Influence of Web Based Digital Media on Citizenship Literacy of Informatics Engineering Students - Sumartono, Sumartono (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
The study aims to analyze the influence of the use of web-based digital learning media on increasing the citizenship literacy of Informatics Engineering students. Civic literacy is understood as a multidimensional competence that includes cognitive, affective, and participatory aspects in the life of the nation and state. The research method used a quantitative approach with a quasi-experimental design of a non-equivalent control group design. The study sample consisted of 58 students, divided into experimental (n=28) and control (n=30) groups. The experimental group received web-based learning over six meetings via a digital platform, while the control group followed conventional learning. The results of the analysis using the t-test showed a significant difference between the experimental group and the control group on the post-citizenship literacy test score (p < 0.001), with an effect size (Cohen's d) of 1.64 which showed a large influence. These findings suggest that web-based learning is effective in strengthening students' understanding and engagement with civic values. The implications of this study emphasize the importance of developing digital media in Citizenship learning to create a generation of critical, ethical, and participatory digital citizens.